Socio-psychological factors associated with anticipated stigma toward COVID-19: a cross-sectional study in Japan - Kana Fujii; Hideki Hashimoto (BMC, 2023)
Abstract Background The stigmatization against COVID-19 has become a public issue. However, it remains unknown which individual factor contributes to anticipated stigma formation. This study explored socio-psychological factors associated with anticipated stigma toward coronavirus disease 2019 (COVID-19). Methods We obtained cross-sectional data regarding 1,638 middle-aged community residents (mean age, 48.5 years) from a population-based survey in metropolitan Tokyo, Japan during the third wave of the COVID-19 pandemic, when a regional public health emergency had been declared in December 2020 and January 2021. We hypothesized that perceived risk of infection, normative beliefs about preventive behaviors, and past experiences of stigmatization unrelated to COVID-19 would be associated with anticipated stigma. Modified Poisson regression was conducted to examine associations after adjustments for demographic and socioeconomic statuses. Results Higher perceived risk (adjusted prevalence ratio [APR] = 1.17; 95% confidence interval [CI, 1.08-1.27]), past experiences of stigmatization (APR = 1.09; 95% CI [1.00-1.19]), and higher normative beliefs about preventive behaviors (APR = 1.18; 95% CI [1.11-1.26]) were independently associated with anticipated stigma. Conclusions These results suggest that intervention messages to increase risk perception and normative beliefs to enhance protective behaviors may have the unintended effect of increasing anticipated stigma in the context of the COVID-19 pandemic.